Pengembangan Video Pembelajaran Pencemaran Lingkungan Berbantuan Prezi melalui Validasi Ahli Media: Development of an Environmental Pollution Educational Video Using Prezi Through Media Expert Validation - Nofita Fajariyanti; Siti Alawiyah; Firly Kurniati (PT Ininnawa Paramacitra Edukasi, 2026)
The rapid development of technology and information has had a significant impact on the use of media in the learning process. ICT-based learning media (Information and Communication Technology) are currently developing in various forms, one of which is audio-visual media based on the Prezi application. The use of interactive learning media is expected to increase students' interest in learning and help them understand the material more effectively. The aim of this study is to develop a video learning resource based on the Prezi application for environmental pollution material. The research method used was Research and Development (R&D), with the research instrument being a media validation sheet. Validasi ini dilakukan oleh dosen Pendidikan IPA untuk mengevaluasi aspek tampilan, isi, keterbacaan, dan kelayakan dari media pembelajaran yang dikembangkan. The results of the validation showed that the Prezi-based video learning media received a rating of 'good' in 70% of cases, 'very good' in 15% of cases, and 'poor' in 10% of cases. These results indicate that the developed learning materials are of good quality and suitable for use in the learning process. Therefore, Prezi-based video learning media can be an alternative, innovative and interactive teaching method for environmental pollution topics, supporting the creation of more engaging and effective learning processes for students